Gendered reporting of household dynamics in the Kenyan dairy sector: Trends and implications for low emissions dairy development - Tavenner, Katie; Fraval, Simon; Omondi, Immaculate A.; Crane, Todd A. (Informa UK Limited, 2018)
Within the Kenyan dairy sector, climate change mitigation interventions are striving to sustainably intensify milk production while addressing the gender dynamics that mediate farmers' ability to effectively participate in, and benefit from, low emissions development. In order to better understand these gender dynamics, household surveys were deployed by the East African Dairy Development (EADD) program to collect information on current practices of decision-making, resources, and labor dynamics within dairy farm households. Using the EADD survey results as secondary data, this study analyzes emergent patterns in these domains among cattle-keeping households in Bomet, Nandi, Uasin Gishu, and Kericho counties in Western Kenya. In analyzing these patterns, paired sample tests revealed statistically significant differences in results based on the gender of the respondent. While there were some categories that women and men reported on similarly, other areas were hotly contested. These results provide important challenges, both methodologically and programmatically, in interpreting gender dynamics across these domains. This paper reflects on the challenges and the opportunities of these data for informing gender-equitable low emissions development in the Kenyan dairy sector.